PERLINDUNGAN HAK-HAK TERSANGKA TERORISME SEBAGAI PERWUJUDAN ASAS PRADUGA TAK BERSALAH DALAM SISTEM PERADILAN PIDANA - Vilano, Danur (Katalogis, 2017)
Research Question : 1. How is the relationship between formulation of protection of rights of accused terrorists and the principle of presumption of innocence in criminal judicial system. 2. How is the relationship between formulation of procedures of treating accused terrorists and the principle of presumption of innocence in criminal judicial system. Research Objectives 1. to identify and analyze the policy on formulation of protection of rights of accused terrorists in the line with the principle of presumption of innocence in criminal judicial system. 2. To identify and analyze the policy on formulation of procedures of treating accused terrorists in the line with the principle of presumption of innocence in criminal judicial system. It was a juridicial normative research with qualitative analysis. Research Finding : The formulation of protection of rights of accused terrorists is normatifvely provided in the Criminal Codes and Law of Terrorism Combat.  The policy on formulation of  protection of the rights of accused  terrorists in  those two laws is not yet fully harmonious since in the Law of Terrorism Combat there is a provision inconsistent with the principles of proof  provided in the Criminal Codes. However, the rest is in general in coherence with the principle of presumption of innocence. The policy on formulation of procedures of treating accused terrorists is already consistent with the principle of protection to the rights of accused terrorists in compliance the Criminal Codes and Law of Terrorism Combat. The policy on formulation of procedures of treating accused terrorists is normatively consistent with the principle of presumption of innocence. However, in their implementations, there were still technical obstacles due to some diffrent perceptions in understanding the provisions concerning with treatment to accused terrorists by the legal enforcers.